[tex] x^{2} +10x+30[/tex]
I always start by moving the last term to the other side
[tex] x^{2} +10x=-30[/tex]
To complete the square you take term 'b' , divide it by 2 then square it
[tex]( \frac{10}{2} )^2[/tex] = 25
We have to add 25 to what we have and what you do to one side you have to do to the other
[tex] x^{2} +10x+25=-30+25[/tex]
[tex] x^{2} +10x+25=-5[/tex]
Now we factor what is on the left side of the equation
[tex](x+5)^2=-5[/tex]
The last step is to move our right side of the equation back over
[tex](x+5)^2+5[/tex] - which is your answer :)))